SiC and GaN power transistors switching energy evaluation in hard and soft switching conditions - Li, Ke; Evans, Paul; Johnson, Christopher Mark (2016)
SiC and GaN power transistors switching energy are compared in this paper. In order to compare switching energy Esw of the same power rating device, a theoretical analysis is given to compare SiC device conduction loss and switching losses change when device maximal blocking voltage reduces by half. After that, Esw of a 650V GaN-HEMT is measured in hard switching condition and is compared with that of a 1200V SiC-MOSFET and a 650V SiC-MOSFET with the same current rating, in which it is shown that Esw of a GaN-HEMT is smaller than a 1200V SiC-MOSFET, which is smaller than 650V SiC-MOSFET. Following by that, in order to reduce device turn-ON switching energy, a zero voltage switching circuit is used to evaluate all the devices. Device output capacitance stored energy Eoss are measured and turn-OFF switching losses are obtained by subtracting Eoss, which shows that GaN-HEMT is sill better than SiC device in terms of switching losses and 1200V SiC-MOSFET has smaller switching losses than 650V SiC-MOSFET.